Monosynaptic targets of utricular afferents in the larval zebrafish - Jia, Yizhen; Bagnall, Martha W. (Frontiers in Neurology, 2022)
The larval zebrafish acquires a repertoire of vestibular-driven behaviors that aid survival early in development. These behaviors rely mostly on the utricular otolith, which senses inertial (tilt and translational) head movements. We previously characterized the known central brainstem targets of utricular afferents using serial-section electron microscopy of a larval zebrafish brain. Here we describe the rest of the central targets of utricular afferents, focusing on the neurons whose identities are less certain in our dataset. We find that central neurons with commissural projections have a wide range of predicted directional tuning, just as in other vertebrates. In addition, somata of central neurons with inferred responses to contralateral tilt are located more laterally than those with inferred responses to ipsilateral tilt. Many dorsally located central utricular neurons are unipolar, with an ipsilateral dendritic ramification and commissurally projecting axon emerging from a shared process. Ventrally located central utricular neurons tended to receive otolith afferent synaptic input at a shorter distance from the soma than in dorsally located neurons. Finally, we observe an unexpected synaptic target of utricular afferents: afferents from the medial (horizontal) semicircular canal. Collectively, these data provide a better picture of the gravity-sensing circuit. Furthermore, we suggest that vestibular circuits important for survival behaviors develop first, followed by the circuits that refine these behaviors.